MODEL PENGELOLAAN WISATA PANTAI MUTIARA MELALUI AKAD MUSYARAKAH DALAM MENINGKATKAN EKONOMI MASYARAKAT - Fauziah, Dianatul; Rohman, Abdur (SIWAYANG Journal: Publikasi Ilmiah Bidang Pariwisata, Kebudayaan, dan Antropologi, 2024)
Mutiara Beach is a tourist destination which opened in 2017 and was officially approved as a tourist destination in 2018. This research was conducted at Mutiara Beach tourism which is located in Tasikmadu Village, Watulimo District, Trenggalek Regency. This study aims to determine the impact of the management model on Mutiara Beach tourism and its impact on improving the community's economy from an Islamic economic perspective. This research was conducted at the Mutiara Beach tour which is located in Tasikmadu Village, Watulimo District, Trenggalek Regency. The research used a qualitative research approach with the case study method. Sources of data come from primary data and secondary data, data collection techniques are carried out by interviewing pearl beach tourism managers and documentation, and data analysis used by researchers is data reduction, data presentation and drawing conclusions. The results showed that 1) the Mutiara Beach tourism management model includes 4 aspects, namely planning, organizing, directing, and supervising a positive impact in improving the community's economy, namely increasing income and employment opportunities; 2) Mutiara Beach tourism uses a musyarakah contract in it’s management between the manager and Perhutani with agreed profit sharing provisions.